2018
DOI: 10.3389/fneur.2018.00472
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Components of the Reach-to-Target Movement After Stroke for Focused Rehabilitation Interventions: Systematic Review and Meta-Analysis

Abstract: Background: Better upper limb recovery after stroke could be achieved through tailoring rehabilitation interventions directly at movement deficits.Aim: To identify potential; targets for therapy by synthesizing findings of differences in kinematics and muscle activity between stroke survivors and healthy adults performing reach-to-target tasks.Methods: A systematic review with identification of studies, data extraction, and potential risk of bias was completed independently by two reviewers. Online databases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 78 publications
(92 reference statements)
0
30
1
Order By: Relevance
“…In the case of single-user classification, our result is similar to the results of the De Vries study, but the multi-user classification showed a substantial lower accuracy. As previously described, stroke survivors show different and more variable movement patterns as compared to healthy controls (21). Additionally, stroke survivors usually experience spasticity which affects their ability to extend their fingers.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the case of single-user classification, our result is similar to the results of the De Vries study, but the multi-user classification showed a substantial lower accuracy. As previously described, stroke survivors show different and more variable movement patterns as compared to healthy controls (21). Additionally, stroke survivors usually experience spasticity which affects their ability to extend their fingers.…”
Section: Discussionmentioning
confidence: 88%
“…Although at the expense of accuracy, grasp movements could be detected up to 1200 ms before the subject touches the object. However, stroke survivors show altered upper limb kinematic movement characteristics within a reach and grasp movement as compared to healthy subjects [21]. Therefore, as a next step, this research needs to be translated such that ultimately the prospective solution could be applied in the gripsupporting glove for stroke if proven useful.…”
mentioning
confidence: 99%
“…Moderately affected stroke patients generally have a larger movement variability than mildly affected stroke patients [182]. When dividing the stroke participants from the present study in two categories for the multi-user classification and comparing the mean accuracies to the first grouped multi-user classification, comparable results for the mild category were achieved, but worse results were found for the moderate category.…”
Section: Discussionmentioning
confidence: 59%
“…In the case of single-user classification, our result is similar to the results of the De Vries study, but the multi-user classification showed a substantially lower accuracy. As previously described, stroke survivors show different and more variable movement patterns as compared to healthy controls [182], which can explain that a multi-user classification method for stroke survivors is not as robust as for healthy subjects with less variable movement patterns.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation